Ceramic coated polypropylene separators for lithium-ion batteries with improved safety: effects of high melting point organic binder. Issue 46 (21st April 2016) - Yu, Linghui; Jin, Yi; Lin, Y. S.
Abstract : A study on Al2 O3 /poly(vinyl alcohol) coated polypropylene separators is presented providing insights into designing high-performance LIB separators with improved safety. Abstract : Coating commercial polyolefin separators with inorganic materials for lithium-ion batteries is considered as one of the most effective and economic ways to enhance the thermal stability of separators which further improves the safety of batteries. The coating usually involves an organic binder, preferably of high melting point (MP) polymer. However, little effort has been devoted to understanding the detailed effects of high MP binders on the thermal behavior of the composite separators as well as on the electrochemical performance of the cells using these separators. In this paper, we present a case study of using a high MP poly(vinyl alcohol) (PVA) binder for ceramic coating (Al2 O3 ) of polyolefin separators. We focus on the effects derived from the use of different contents of PVA. We also compare the effects of PVA and a commonly used low MP poly(vinylidene fluoride) binder. PVA is more effective in improving the thermal stability of the separators than PVDF. Increasing the PVA content increases the pore tortuosity and decreases the wettability of the coating layer, compromising the cell performance. To obtain high-performance composite separators, one will need to use a binder with a high MP, good electrolyte wettability and strong bonding with the coating particles. The binder content should be well controlled. Constructing a coating layer with low tortuosity will be greatly beneficial for cell performance. This study provides insights into designing high-performance composite separators with improved safety.